Constructionism and Constructivism in Computational Thinking and Mathematics Education: Bibliometric Review - Edi Supriyadi; Jarnawi Afgani Dahlan (Universitas Sebelas Maret, 2022)
This study intends to carry out a bibliometric analysis to answer the following research questions: What is the annual increase in publications of constructionism, constructivism, and computational thinking, and mathematics education?; Who are the most prolific writers of constructionism, constructivism, computational thinking, and mathematics education?; Which the most countries in the fields of constructivism, constructivism, computational thinking, and mathematics education?; Who are the most frequently cited scientists? In the end, the biblioAnalysis function generates descriptive data from bibliographic data. Thus, this description has explained that these keywords are sufficient to describe the use of theory in learning computational thinking and mathematics. After we have completed our mapping, we will have a combined framework at our disposal, which will allow us to gain a deeper understanding of the possible connections that exist between constructionism, constructivism, computational thinking, and mathematics education.